Evaluation of the Turkish translation of a disease activity form for Behcet's syndrome - (:unkn) unknown (OXFORD UNIV PRESS, 1999)
Objective. This study examined the interobserver and intra-observer reliability of the Turkish version of the Behcet's Disease Current: Activity Form (BDCAF), which was obtained by a translation and back-translation process. Methods. Fifty Behcet's syndrome (BS) patients were assessed by four rheumatologists in separate morning and afternoon sessions. Results. The results showed good intra- and interobserver agreement for the oro-genital ulcers and eye involvement of BS, but there was poor agreement between (kappa score = 0.14) and within observers (range for kappa scores 0.09-0.25) for their overall impression of disease activity, individual low kappa scores were also noted for erythema nodosum, vascular involvement, central nervous system involvement and gastrointestinal involvement. Conclusion. These results suggest that the Turkish version of BDCAF may be useful for assessing the classic triad of BS toro-genital ulceration and eye involvement), but more experience is needed for its other parts.
Keywords: Behcet's syndrome; disease activity; Behcet's Disease Current Activity Form; Turkish translation; reliability analysis